PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI MAN 1 PONTIANAK (PENA KREATIF : JURNAL PENDIDIKAN, 2023)
This study aims to improve student learning outcomes in English subjects at MAN 1 Pontianak by using the Two Stay Two Stray Learning Model. This research is motivated by 1) student learning outcomes in English subjects are still below the minimum completeness criteria (KKM), 2) Teachers tend to use conventional learning models in learning. This research uses classroom action research (CAR). The study was conducted at MAN 1 Pontianak in class XII MIPA 2. The number of samples in this study was 38 students consisting of 13 boys and 25 girls. This research was carried out in two cycles each in two meetings. Data collection techniques using a written test. The results showed that there was an increase in student learning outcomes in English subjects from the first cycle by 21.05%, increasing to 76.32% in the second cycle with the Two Stay Two Stray learning model.